The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1136/emermed-2012-202089
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation in acute pulmonary embolism: prognostic considerations

Abstract: The presence of AF, irrespective of its timing, may independently predict mortality in patients with acute PE. These data should be tested and validated in prospective studies using larger cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 24 publications
0
38
0
2
Order By: Relevance
“…Twenty studies (4898 patients) reported data on in‐hospital mortality . Several ECG features were meta‐analyzed for this outcome (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies (4898 patients) reported data on in‐hospital mortality . Several ECG features were meta‐analyzed for this outcome (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the GRACE score and other clinical rules (LR-PED), atrial fibrillation may be an independent predictor of 6-month mortality in patients with acute pulmonary embolism; however, these data should be tested and validated in prospective studies using larger cohorts (28, 29). In our study, although the prevalence of atrial fibrillation was 37.9%, the difference between the survivor and non-survivor groups was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of atrial fibrillation in acute pulmonary embolism (PE) varies widely, and most studies are focused on diagnostic purposes . Moreover, as the temporal sequence of events has not been determined in these studies, the question of cause and effect remains unanswered.…”
Section: Introductionmentioning
confidence: 99%